The Effect of Blended Learning Models Assisted by Video Tutorials on Students' Critical Thinking Ability in Mathematics Learning - Eline Yanty Putri Nasution; Laras Sintia; Rahmi Putri (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2022)
This study aimed to determine students' critical thinking skills on the subject of number patterns using the Blended Learning learning model. The research was conducted at MTsN 3 Kerinci, Academic Year 2021/2022. The research method used is a quasi-experimental method with a posttest-only control design. The research instrument used is a critical thinking ability test. The results showed that the critical thinking ability of students who were taught with the Blended Learning leraning model assisted by video tutorials had an average score of 8.58, and the class that did not use the Blended Learning learning model assisted by video tutorials had an average score of 6.24. Thus, this study concludes that the Blended Learning learning model has a significant influence on students' critical thinking ability.